Writing science before the Greek s a naturalistic analysis of the Babylonian astronomical treatise MUL.APIN - Watson, Rita, 1949- (Culture and History of the Ancient Near East, 2011)
The beginnings of written science have long been associated with classical Greece. Yet in ancient Mesopotamia, highly-sophisticated scientific works in cuneiform script were in active use while Greek civilization flourished in the West. The subject of this volume is the astronomical series MUL.APIN, which can be dated to the seventh century BCE and which represents the crowning achievement of traditional Mesopotamian observational astronomy. Writing Science before the Greeks explores this early text from the perspective of modern cognitive science in an effort to articulate the processes underlying its composition. The analysis suggests that writing itself, through the cumulative recording of observations, played a role in the evolution of scientific thought. \'All in all, the authors should be congratulated for this groundbreaking study. Apart from significant new insights into MUL.APIN it has opened up a new avenue for research on ancient scientific texts that is likely to yield further interesting results, particularly if the cognitive analysis is combined with other approaches.\' Mathieu Ossendrijver, Humboldt University